What do firm managers tell us about the transmission channels of oil price shocks? - Dirk Drechsel; Heiner Mikosch; Samad Sarferaz; Matthias Bannert (ETH Zurich, KOF Swiss Economic Institute, 2022)
In this paper, we investigate the transmission channels of oil price shocks using a factorial survey. We confront CEOs and CFOs of a representative sample of firms with a hypothetical vignette in which the oil price rises exogenously above managers' baseline expectations. The managers then estimate the short- and medium-term cost, price, and output effects of the shock on their firms. We find that the managers expect the shock to have very different effects on their firms: the cross-sectional distributions of the responses are large, skewed, and have fat tails. Higher firm-specific energy input costs lead managers to expect greater output losses and sales price increases. Higher market power accelerates this input cost effect. Another important determinant is managers' pre-shock uncertainty about business prospects. The importance of the three channels varies considerably across industries.
hdl:20.500.11850/584846
Keywords: C83; D22; D84; E31; E32; 330; Oil price shocks; transmission channels; firms; expectations; surveys; vignettes